Insulin and Exendin-4 Reduced Mutated Huntingtin Accumulation in Neuronal Cells - Rea, Silvia; Della-Morte, David; Pacifici, Francesca; Capuani, Barbara; Pastore, Donatella; Coppola, Andrea; Arriga, Roberto; Andreadi, Aikaterini; Donadel, Giulia; Di Daniele, Nicola; Bellia, Alfonso; Lauro, Davide (Frontiers in Pharmacology, 2020)
Several studies reported the association between Huntington Disease (HD), an autosomal dominant disorder due to the accumulation of mutated Huntingtin (HTT), and Diabetes Mellitus (DM). Moreover, it is well established as diabetic patients are more prone to develop neurodegeneration and cognitive decline. In a study conducted on diabetic mice, we demonstrated as HTT played a central role as metabolic regulator, highlighting a pathological loop between DM and HD. Furthermore, it has also been described as intranasal insulin (Ins) administration improved cognitive functions in patients with neurodegenerative disorders such as Alzheimer Disease, and as Exendin-4 (Ex-4) enhanced lifespan and ameliorated glucose homeostasis in mice model of HD. However, the molecular mechanisms are still missing. Therefore, the aim of the present study was to investigate the intracellular pathways underlay the neuroprotective effect of these hypoglycemic drugs by using an in vitro model of HD, composed by dopaminergic neurons treated with the neurotoxic compound 6-hydroxydopamine (6-ohda). The obtained results showed as 6-ohda increased mHTT expression and reduced HTT phosphorylation at Ser421, post-translational modification able to protect against mHTT accumulation. Moreover, the pre-treatment with Ex-4 or Ins reverted the harmful effect induced by 6-ohda by activating AKT1 and SGK1 kinases, crucial nodes of insulin pathway, and by reducing the phosphatase PP2B, which generally dephosphorylates HTT contributing to mHTT neurotoxic effect. In conclusion, our data highlighted as Ex-4 and Ins are able to counteract the neurotoxic effect induced by mHTT, opening novel pharmacological therapies against neurometabolic disorders with main focus on HD, which is still considered an orphan illness.